Pengaruh Merek Terhadap Keputusan Pembelian Konsumen Sepeda Motor Honda Pada PT. Daya Anugrah Mandiri Cabang Sungai Bahar Kab. Muaro Jambi - Aiga Ria Raharja (Science of Management and Students Research Journal (SMS), 2019)
This study aims to determine how the influence of brands on consumer purchasing decisions like Honda motorcycles at PT. Daya Anugrah Mandiri in Sungai Bahar. Muaro Jambi. For the analyze how make the brand towards consumer purchasing decisions like Honda motorcycles at PT. Daya Anugrah Mandiri in Sungai Bahar. Muaro Jambi. This study uses a descriptive qualitative method with a form of correlational research, that explains the relationship of independent variables to the dependent variable. The analysis tool in this study uses simple linear regression with proof of the hypothesis by statistical tests -t. the results of the study show that the brand has a positive and significant effect on consumer purchasing decisions where it is indicated by t count > t table. While the correlation value of 87.4% means that there is a very close relationship between brand variables and variable consumer purchasing decisions.